Aplicação de solventes eutéticos profundos hidrofóbicos na determinação de parabenos e bisfenol A em amostras de lodo de esgoto usando cromatografia gasosa acoplada à espectrometria de massas com introdução da amostra via pirolisador - Ferreira, Karen Chibana [UNESP] (2024)
The presence of emerging contaminants (ECs) has been the subject of discussions due to concerns about the risks these compounds pose to human health and the environment. In this context, the pursuit of environmentally sustainable analytical methods has been considered essential. One response to this demand has been the recent generation of solvents, including hydrophobic deep eutectic solvents (HDES), which have been prepared by combining two or three precursors, establishing intermolecular hydrogen bonds between a donor species (HBD) and an acceptor species (HBA). Thus, the main objective of the study was to contribute to the advancement of sustainable analytical methods, providing an efficient approach for the detection and quantification of ECs in environmental samples, such as sludge, using HDES as extracting solvents. The characterization of these solvents involved the evaluation of parameters such as density and viscosity, as well as the use of Fourier-transform infrared spectroscopy (FTIR). The preparation of HDES from precursors such as DL-menthol (HBA) and organic acids (decanoic, dodecanoic, acetic), acting as HBDs, was quick and simple, involving heating the mixture at 60°C for 20 minutes followed by cooling to room temperature. All HDES were clear, except for dodecanoic acid, which exhibited a yellowish color due to the precursor used. Despite having a density lower than water, facilitating the collection of the organic phase for analysis, HDES had higher viscosity compared to water. Characterization by FTIR and thermoanalytical analyses confirmed the formation of the solvent, evidenced by the presence of the hydroxyl (O─H) absorption band and endothermic events indicating lower melting points of HDES compared to their pure precursors. Factorial design analyzed temperature, time, and sample volume for application in the determination of methylparaben (MeP), propylparaben (PrP), butylparaben (BuP), and bisphenol A (BPA). Chemometric tools indicated that the analytical response was directly proportional to the increase in injection volume, with the ideal value being 20 μL. In dispersive liquid-liquid microextraction (DLLME), the optimal conditions were 300 μL of HDES, 350 μL of ACN as a dispersing solvent, pH equal to 10, sludge dilution by 50 times, and 27% m/v of NaCl. Evaluation of the figures of merit indicated a recovery rate exceeding 90%, intra- and inter-day precisions below 15%, and the limit of detection (LOD) established in the range of 25 to 50 μg L-1. The method demonstrated selectivity, avoiding interferents in the analytical response. The application of HDES in environmental matrices allowed the determination of emerging contaminants, following the principles of sustainable analytical chemistry, which was confirmed by applying the AGREE evaluation metric system, resulting in values of 0.72 and 0.76 corresponding to the method used and sample preparation.